Company Liability and Competition Law: Exposure of Company to Risk of Undesirable Behaviour of Directors - Caliskan, Samet (Springer Netherlands, 2019)
In order to protect the objectives of competition policy, companies as undertakings are primarily targeted for the competition law infringements based on the mixed approach of compliance and deterrence theories relying on the view that company directors are incentivised to comply with the rules of competition law by the internal compliance programmes and corporate fines are the consequences of incompliance. This enforcement strategy gives rise to a tension between corporate governance, company law and competition law, as the former two focus on the behaviour of individuals within the corporate structure, while the latter concerns the impact of the company’s behaviour in the market. The question that arises in this tension is whether or to what extent competition law actually considers the way in which the company is run internally while it seeks to promote these primary objectives. This article analyses the deterrent effectiveness of primary enforcement strategy employed in the UK competition law regime and argues that competition law does not tend to localise the source of conduct or particular decisions and does not aim to correct the right wrongdoer. Despite that lack of effectiveness of public enforcement strategy to deter further anti-competitive behaviour has led individual sanctions to be introduced by the Enterprise Act 2002 and the Enterprise and Regulatory Reform Act 2013 in the UK, companies are still primarily targeted by corporate fines even though directors have intentionally breached the rules of competition law and this strategy is unlikely to deter directors from engaging with undesirable behaviour which exposes the company to risk of liability and loss. © 2019, Springer Nature B.V.
Keywords: Company; Compliance; Deterrence; Directors; Public enforcement; Regulatory infringements